Changes and continuities in police responses to domestic abuse in England and Wales during the Covid-19 ‘lockdown’ - Walklate, Sandra (Policing and society, 2022)
Covid-19 and the associated public health response directing people to stay at home and/or shelter in place generated acute awareness of, and concerns about, the likely impact on violence(s) against women across the globe. Initial reports from support services suggested that such violence increased, and that its impact was more complex. Early evidence of increased demands in relation to domestic abuse on policing was however less clear. This paper, based on findings from a larger project, offers an analysis of the initial responses to domestic abuse by the police and the courts in England and Wales during the initial pandemic lockdown of 2020. These findings are situated within wider debates concerned with the nature and impact of the current organisational structure of policing and suggests that whilst police forces responded both quickly and innovatively in order to maintain a focus on domestic abuse, their capacity to continue in this vein will be limited in the absence of wider structural and organisational change.